O princípio da colaboração intersubjetiva no processo civil brasileiro : uma análise acerca da sua influência no poder geral de cautela do juiz - Marinho, érika de Sá (2008)
This search is on the scope of procedural law and takes as assumption identify the existence of the principle of collaboration intersubjective in civil procedure Brazil, promoting an analysis about its influence on the general power of caution of the judge as a way to ensure the outcome of the process useful. Search is still, see the changes that are already suffering the legal system, directing the search for greater consideration when the purpose of the procedural tool on the new cooperative attitude of the judge. It is also a critical study regarding the issue of time and legal formalism sharp under the legal relationship procedure, which impede the exercise of a provision court faster and efficient. The achievement of results and effective materialization of the rights are just ends of the process to be pursued by the parties, servers, experts, interpreters and judges reflecting the influence of the principle of collaboration intersubjective, Marked by discretionary attitude of the judge in the process and that, implicitly, can already be identified in several devices of our Code of Civil Procedure. The fight against abusive practices, the length of the court provision enabling efficient implementation of this as an expression of the principle of collaboration and the activism of the judiciary is proposing that this work of research